2014
DOI: 10.1155/2014/867106
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Nanosilica Aerogel with Phosphorus Flame Retardants on Improving Flame Retardancy and Leaching Resistance of Wood

Abstract: Nanosilica (Nano-SiO 2 ) sol fabricated by a sol-gel process was introduced into wood modification with phosphorus flame retardants to improve the flame retardancy and leaching resistance of wood. The obtained materials were characterized by scanning electron microscopy and energy dispersive spectrometer (SEM-EDS), thermogravimetric analysis (TGA), cone calorimetric (CONE), and infrared spectroscopy (FT-IR). The residual rate of flame retardants before and after leaching was determinated by a leaching resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…As can be seen in Figure 1(b), the OGW began to decompose at onset and peak at 179 ∘ C and 270 ∘ C, respectively, while the MGW started to decompose at 213 ∘ C and 287 ∘ C for onset and peak, respectively. It is interpreted that MGW is reasonably able to retard processing loss weight from 270 to 287 ∘ C. Zhu et al [7] have demonstrated a synergistic effect of silica aerogel with temperature increments of about 12 ∘ C-17 ∘ C. At temperatures higher than 270 ∘ C, the addition of silica aerogel reduced the rate of weight loss of the blanket. Doping with silica aerogel particles caused the weight loss to change slightly compared with OGW sample, which was associated with an increase in the amount of silica ash generated during the test which effectively improves thermal stability of the silica aerogel blanket.…”
Section: Derivative Thermogravimetry (Dtg)mentioning
confidence: 96%
“…As can be seen in Figure 1(b), the OGW began to decompose at onset and peak at 179 ∘ C and 270 ∘ C, respectively, while the MGW started to decompose at 213 ∘ C and 287 ∘ C for onset and peak, respectively. It is interpreted that MGW is reasonably able to retard processing loss weight from 270 to 287 ∘ C. Zhu et al [7] have demonstrated a synergistic effect of silica aerogel with temperature increments of about 12 ∘ C-17 ∘ C. At temperatures higher than 270 ∘ C, the addition of silica aerogel reduced the rate of weight loss of the blanket. Doping with silica aerogel particles caused the weight loss to change slightly compared with OGW sample, which was associated with an increase in the amount of silica ash generated during the test which effectively improves thermal stability of the silica aerogel blanket.…”
Section: Derivative Thermogravimetry (Dtg)mentioning
confidence: 96%
“…Silica aerogel with ultra-low density and highly crosslinking structure has been regarded as one of the most efficient thermal insulating materials in addition to its excellent flame retardancy [3,4]. Due to its attractive features of thermal insulation and flame retardancy, silica aerogel has been extensively applied to wood [1,5,6], fiber-reinforced composites [7][8][9][10], cement-based composites [11,12], glass materials [13] and other nanocomposites [14]. To date, wood modified with silica aerogels is mainly by means of in situ synthesis [1,6] or impregnation with sol [5].…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 8 also shows that the FT-IR image of bamboo treated with AB and ABS has an absorption band generated by P=O stretching vibration at 1250-1253 cm -1 , (Zhu et al 2014) which means that ADP has entered the interior of the bamboo.…”
Section: Tg Analysismentioning
confidence: 94%
“…Nano-SiO 2 sol is a colloidal solution with a micelle diameter of 10-100 nm, and it has adsorption and blocking action when dried and solidified into gel (Lou et al 2010), which shows a porous structure when added to the interior of the material. Meanwhile, nano-SiO 2 and nitrogen-phosphorus fire retardants can play a synergistic role in fire retardant and smoke suppression properties (Zhu et al 2014, Altun et al 2010. What is more, nano-SiO 2 gel has large specific surface area and strong adsorption properties, which may help to prevent water-based fire retardant from running off.…”
Section: Introductionmentioning
confidence: 99%